Infarct size by contrast enhanced cardiac magnetic resonance is a stronger predictor of outcomes than left ventricular ejection fraction or end-systolic volume index: prospective cohort study - Wu, E; Ortiz, J T; Tejedor, P; Lee, D C; Bucciarelli-Ducci, C; Kansal, P; Carr, J C; Holly, T A; Lloyd-Jones, D; Klocke, F J; Bonow, R O (Heart (British Cardiac Society), 2008)
Objectives:Ejection fraction (EF) and end-systolic volume index (ESVI) are established predictors of outcomes following ST-segment elevation myocardial infarction (STEMI). We sought to assess the relative impact of infarct size, EF and ESVI on clinical outcomes and left ventricular (LV) remodelling.Design:Prospective cohort study.Setting:Academic hospital in Chicago, USA.Patients:122 patients with STEMI following acute percutaneous reperfusion.Main outcome measures:Death, recurrent myocardial infarction (MI) and heart failure.Methods:Cardiac magnetic resonance imaging was obtained within 1 week following STEMI in 122 subjects. ESVI, EF and infarct size were tested for the association with outcomes over 2 years in 113 subjects, and a repeat study was obtained 4 months later to assess LV remodelling in 91 subjects.Results:Acute infarct size correlated linearly with the initial ESVI (r = 0.69, p<0.001), end-diastolic volume index (EDVI) (r = 0.42, p<0.001) and EF (r = −0.75, p<0.001). All were independently associated with outcomes (one death, one recurrent MI and 16 heart failure admissions). However, infarct size was the only significant predictor of adverse outcomes (p<0.05) by multivariate analysis. The smallest infarct size tertile had an increased EF (49% (SD 8%) to 53% (6%); p = 0.002) and unchanged EDVI (p = 0.7). In contrast, subjects with the largest infarct tertile also had improved EF (32% (9%) to 36% (11%); p = 0.002) at the expense of a dramatic increase in EDVI (86 (19) to 95 (21) ml/m2; p = 0.005).Conclusions:Infarct size, EF and ESVI can predict the development of future cardiac events. Acute infarct size, which is independent of LV stunning and loading, directly relates to LV remodelling and is a stronger predictor of future events than measures of LV systolic performance.